Recovery experiences among mental health service users going through the Balancing Everyday Life™ intervention – A deductive qualitative study - Mona Eklund; Elisabeth Argentzell (Scandinavian Journal of Occupational Therapy)
Background The occupational therapy intervention Balancing Everyday Life (BEL)TM aims to support mental health service users towards improved occupational balance and personal recovery. Yet, no research has specifically addressed recovery experiences among BELTM participants.Aim To investigate how the recovery process was experienced by mental health services users who had participated in BELTM.Methods The study was based on qualitative interviews with 11 participants. A deductive content analysis was performed based on the CHIME framework, a research-based tool for characterising the recovery process.Results All categories and most subcategories described in the CHIME framework could be found in the participants’ experiences. The most prominent categories were Sense of connectedness and Empowerment. Most subcategories were identified as well. Additionally, two subcategories not covered in CHIME were distinguished – occupational balance, and self-esteem and self-confidence – which may be specific to an occupational therapy intervention like BELTM.Conclusion The study showed that CHIME was relevant for characterising the recovery process among BELTM participants and identifying the features shaping that process. The findings support CHIME, while also indicating that BELTM offers some additional avenues for personal recovery.Significance An occupational therapy intervention can support mental health service users towards personal recovery.